L’apport du concordancier à l’analyse et à la remédiation des erreurs des apprenants dans les forums de discussion en ligne - Joseph Rézeau (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
In the past 25 years, the increasing user-friendliness of concordance software and availability of digital corpora have favoured the development of corpus linguistics. The use of such tools and corpora with a view to analysing language learners’ production is more recent ([Granger98]; [ChambersOSullivan04]). With the rapid increase of online courses, of which discussion forums are an essential component, language teachers now have access to large digital corpora which can be used to analyse the characteristics of their students’ semi-spontaneous productions. In this article we shall use examples of online discussions of French-speaking students of English to demonstrate how a concordancer can help teachers analyse their students’ typical language errors in order to remedy them.